Chaos-based Cryptography for Voice Communication Security - S, Smrithi K; V, Jisha K (IRO Journal on Sustainable Wireless Systems, 2024)
Chaos-based cryptography represents a groundbreaking approach to securing voice communications, leveraging chaotic systems to integrate unpredictability and randomness into encryption keys. This innovative methodology protects against eavesdropping, man-in-the-middle (MitM) attacks, and spyware, safeguarding sensitive conversations. By utilizing chaos theory to encrypt voice signals, Chaos- based cryptography strictly limits access to authorized parties, maintaining confidentiality and data integrity. Notably, this chaos-based encryption framework delivers exceptional voice transmission speed and reliability, making it ideal for critical applications demanding high communication velocity and precision. Chaos- based cryptography also adheres to regulatory standards for secure communication, guaranteeing compliance across various industries. Consequently, this cutting-edge technology is highly sought after for enhancing voice communication system security. The study presents an overview of the chaos- based cryptography for voice communication security.
Keywords: Chaos- based cryptography; Chaos Theory; Randomness; Data Integrity